‘Banda Terrane’ basement and cover in the Noil Meto River section, southern West Timor (Timor Barat, Nusa Tenggara Timur, Indonesia) - Charlton, Tim Richard; Titu-Eki, Adept Talan (Berita Sedimentologi, 2023)
A previously undocumented body of Mutis metamorphic complex is reported from the Noil Meto River, approximately 7km south of Soe town in southern West Timor. Cover sequences overlying the Mutis Complex include the Cretaceous Haulasi Formation (the upper element of the Palelo Group) which most likely has an unconformable relationship to the metamorphic complex; and (possibly) the Permian Maubisse Formation which may overlie the Mutis Complex with an unresolved stratigraphic or structural contact. This is the first substantial documentation of the Mutis Complex and the Palelo Group to the south of the Central Basin. These elements of the so-called Banda Terrane, widely considered allochthonous ‘Asiatic’ elements, are overthrust by Triassic-Jurassic cover sequences (Aitutu and Wai Luli Formations) of the Australian continental margin succession.